Comparative Whole Genome Analysis of Escherichia coli O157:H7 Isolates From Feedlot Cattle to Identify Genotypes Associated With the Presence and Absence of stx Genes - Jia, Mo; Geornaras, Ifigenia; Martin, Jennifer N.; Belk, Keith E.; Yang, Hua (Frontiers in Microbiology, 2021)
A comparative whole genome analysis was performed on three newly sequenced Escherichia coli O157:H7 strains with different stx profiles, previously isolated from feedlot cattle (C1-010 [stx1-, stx2c+], C1-057 [stx-] and C1-067 [stx1+, stx2a+]), as well as five foodborne outbreak strains and six stx-negative strains from NCBI. Phylogenomic analysis demonstrated that the stx2c-carrying C1-010 and stx-negative C1-057 strains were grouped with the six NCBI stx-negative E. coli O157:H7 strains in Cluster 1, while the stx2a-carrying C1-067 strain and the five foodborne outbreak strains, were clustered together in Cluster 2. Based on different clusters, we selected the three newly sequenced strains, one stx2a-carrying strain and the six NCBI stx-negative strains and identify their prophages at stx insertion sites. All stx-carrying prophages contained both the three Red recombination genes (exo, bet, gam) and their repressor cI. On the other hand, the majority of the stx-negative prophages carried only the three Red recombination genes but their repressor cI was absent. In the absence of the repressor cI, the consistent expression of the Red recombination genes in prophages might result in more frequent gene exchanges, potentially increasing the probability of acquisition of stx genes. We further investigated each of the ten selected E. coli O157:H7 strains for their respective unique metabolic pathway genes. Seven unique metabolic pathway genes in the two stx2a-carrying strains and one in the single stx2c-carrying and seven stx-negative strains were found to be associated with an upstream insertion sequence 629 within a conserved region among these strains. Presence of more unique metabolic pathway genes in stx2a-carrying E. coli O157:H7 may potentially increase their competitiveness in complex environments such as feedlot cattle. For the stx2c-carrying and stx-negative E. coli O157:H7 strains, the fact that they were grouped into the same phylogenomic cluster and had the same unique metabolic pathway genes suggested that they may also share closely related evolutionary pathways. As a consequence, gene exchange between them is more likely to occur. Results from this study could potentially serve as a basis to help develop strategies to reduce the prevalence of pathogenic E. coli O157:H7 in livestock and downstream food production environment.